Influence of Imaging Features and Technique on US-guided Tattoo Ink Marking of Axillary Lymph Nodes Removed at Sentinel Lymph Node Biopsy in Women With Breast Cancer. Issue 5 (25th August 2021) - Pajcini, Marlen; Wapnir, Irene; Tsai, Jacqueline; Edquilang, Joanne; DeMartini, Wendy; Ikeda, Debra
Abstract: Objective: To describe tattoo ink marking of axillary lymph nodes (TIMAN) and the elements leading to successful removal at sentinel lymph node biopsy (SLNB). Methods: An IRB-approved retrospective image review was conducted of breast cancer patients who underwent SLNB after TIMAN from February 2013 to August 2017, noting patient and tattooed lymph node (TLN) features, initial biopsy type, time to surgery, if the TLN was identified at surgery, and correlation with the SLN. Cases were divided into two groups: the presurgical group, which had primary surgery, and the pre-neoadjuvant chemotherapy (NACT) group, which underwent surgery after completing NACT. Results: Of 30 patients who underwent 32 TIMAN procedures, 10 (33.3%) were presurgical and 20 (66.7%) were pre-NACT. The average lymph node (LN) depth from the skin was 1.6 cm, with an average of 0.3 mL of tattoo ink injected. Of 32 procedures, 29 (90.6%) had US images demonstrating the injection. Of these, 10 (34.5%) were injected in the LN cortex surface and 19 (65.5%) in the middle cortex. Seven (24.1%) were injected in the LN lateral aspect, 12 (41.4%) in the mid aspect, and 10 (34.5%) in the medial aspect. Of 32 LNs, 28 (87.5%) were tattooed immediately after initial biopsy and 4 (12.5%) at a later date. At SLNB, all 32 (100%) TLNs were identified, all correlated with the SLN, and 10 (31.3%) were positive for cancer. Conclusion: Using an average of 0.3 mL of tattoo ink, all TLNs were successfully identified for removal at surgery, despite variability in LN and injection factors. Graphical Abstract: